Completion and Publication Rates of Randomized Controlled Trials in Surgery: An Empirical Study. Issue 1 (July 2015) - Rosenthal, Rachel; Kasenda, Benjamin; Dell-Kuster, Salome; von Elm, Erik; You, John; Blümle, Anette; Tomonaga, Yuki; Saccilotto, Ramon; Amstutz, Alain; Bengough, Theresa; Meerpohl, Joerg J.; Stegert, Mihaela; et al.
Abstract : Objective: To investigate the prevalence of discontinuation and nonpublication of surgical versus medical randomized controlled trials (RCTs) and to explore risk factors for discontinuation and nonpublication of surgical RCTs. Background: Trial discontinuation has significant scientific, ethical, and economic implications. To date, the prevalence of discontinuation of surgical RCTs is unknown. Methods: All RCT protocols approved between 2000 and 2003 by 6 ethics committees in Canada, Germany, and Switzerland were screened. Baseline characteristics were collected and, if published, full reports retrieved. Risk factors for early discontinuation for slow recruitment and nonpublication were explored using multivariable logistic regression analyses. Results: In total, 863 RCT protocols involving adult patients were identified, 127 in surgery (15%) and 736 in medicine (85%). Surgical trials were discontinued for any reason more often than medical trials [43% vs 27%, risk difference 16% (95% confidence interval [CI]: 5%–26%); P = 0.001] and more often discontinued for slow recruitment [18% vs 11%, risk difference 8% (95% CI: 0.1%–16%); P = 0.020]. The percentage of trials not published as full journal article was similar in surgical and medical trials (44% vs 40%, risk difference 4% (95% CI: −5% to 14%); P = 0.373). Discontinuation of surgical trials was a strong risk factor for nonpublication (odds ratio = 4.18, 95% CI: 1.45–12.06; P = 0.008). Conclusions: Discontinuation and nonpublication rates were substantial in surgical RCTs and trial discontinuation was strongly associated with nonpublication. These findings need to be taken into account when interpreting surgical literature. Surgical trialists should consider feasibility studies before embarking on full-scale trials. Abstract : Supplemental Digital Content is Available in the Text.We evaluated early discontinuation and nonpublication of surgical trials approved in Canada, Germany, and Switzerland. Forty-three percent were stopped early, 18% for slow recruitment. Trial discontinuation was strongly associated with nonpublication. These findings are relevant when interpreting surgical literature, and surgical trialists should consider feasibility studies before starting full-scale trials.